A prospective, randomized, open-label study comparing the efficacy and safety of clonazepam versus nortriptyline on quality of life in 40+ years old women presenting with restless leg syndrome - Roshi; Vishal R Tandon; Annil Mahajan; Sudhaa Sharma; Vijay Khajuria (Wolters Kluwer Medknow Publications, 2018)
Introduction: Restless legs syndrome (RLS) is a neurological disorder characterized by an urge to move the legs usually accompanied by unpleasant leg sensations. RLS also impacts health related quality of life (QOL) in patients suffering from it. Further, it affects women more than men. Although a voluminous literature of studies is available evaluating the role of benzodiazepines (clonazepam and antidepressant (nortriptyline) in the treatment of RLS, but to the best of our knowledge, no comparative study is available comparing both of these drugs for efficacy and safety for the treatment of RLS QoL among 40 + years old women. Materials and Methods: A prospective, randomized, open label comparative study was conducted in Postgraduate Department of Pharmacology in collaboration with the Department of General Medicine, Government Medical College, Jammu, a tertiary care teaching hospital for 1 year. Conclusion: Clonazepam proved to be significantly better in improving RLSQoL score. Difference between respective baselines of both groups was statistically insignificant.